2021
DOI: 10.3389/fimmu.2021.675731
|View full text |Cite
|
Sign up to set email alerts
|

High Mobility Group Box 1 (HMGB1) Induces Toll-Like Receptor 4-Mediated Production of the Immunosuppressive Protein Galectin-9 in Human Cancer Cells

Abstract: High mobility group box 1 (HMGB1) is a non-histone protein which is predominantly localised in the cell nucleus. However, stressed, dying, injured or dead cells can release this protein into the extracellular matrix passively. In addition, HMGB1 release was observed in cancer and immune cells where this process can be triggered by various endogenous as well as exogenous stimuli. Importantly, released HMGB1 acts as a so-called “danger signal” and could impact on the ability of cancer cells to escape host immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…We used the THP-1 cell line (monocytic leukemia) and more premature primary human acute myeloid leukemia (AML) blasts. In THP-1 cells, TGF-β is known to highly upregulate galectin-9 expression in a Smad3-dependent manner (a significant increase in Smad3 phosphorylation induced by TGF-β was also reported for these cells) (3,20). Furthermore, THP-1 cells do not express detectable amounts of granzyme B protein and do not show detectable catalytic activity of this enzyme (9).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…We used the THP-1 cell line (monocytic leukemia) and more premature primary human acute myeloid leukemia (AML) blasts. In THP-1 cells, TGF-β is known to highly upregulate galectin-9 expression in a Smad3-dependent manner (a significant increase in Smad3 phosphorylation induced by TGF-β was also reported for these cells) (3,20). Furthermore, THP-1 cells do not express detectable amounts of granzyme B protein and do not show detectable catalytic activity of this enzyme (9).…”
Section: Resultsmentioning
confidence: 90%
“…With monocytic AML cells, which do not express detectable amounts of granzyme B protein ( 9 ), this biological response has probably more complex reasons. THP-1 cells secrete high levels of galectin-9, especially when pre-treated with PMA or other triggers of exocytosis (such as latrotoxin, or Toll-like receptor (TLR) ligands) ( 20 ). They are also capable of secreting VISTA.…”
Section: Discussionmentioning
confidence: 99%
“…In the early stage of metastasis, autophagy mainly suppresses the occurrence of metastasis by regulating the anti‐tumor immune response. 213 , 214 , 215 Autophagy‐related protein 5(ATG5) is considered to be closely related to autophagy. In pancreatic ductal adenocarcinoma, mice with ATG5 knockout developed more tumors and metastases than control mice.…”
Section: Components and Mechanisms Involved In Metastasismentioning
confidence: 99%
“… 214 In addition, studies have found that autophagy can stimulate tumor‐related spontaneous inflammation by releasing high mobility group box 1 and enhance the antitumor immune response of DCs to limit metastasis. 215 In the later stage of tumor metastasis, autophagy reduces the adhesion between tumor cells and ECM by regulating the activity of the Rho family so as to promote tumor migration and invasion. 216 In addition, autophagy can enhance tumor invasion and promote the progress of tumor metastasis by inhibiting anoikis of CTCs, maintaining the stemness of CSCs, and reawakening dormant tumor cells.…”
Section: Components and Mechanisms Involved In Metastasismentioning
confidence: 99%
“…Therefore, we speculated that the inhibition role of MS19 on HMGB1 secretion is partially mediated through NF-κB signaling and TNF-α-dependent mechanism, since that ODN exhibited a strong inhibition against the NF-κB activation and TNF-α production in this study. In addition, after its release, extracellular HMGB1 usually acts as a DAMP molecule and transmits signals to the cell interior via the activation of receptors including TLR4, resulting in the formation of a positive feedback loop that potentially amplifies local inflammatory responses ( Su et al, 2021 ; Teo Hansen Selno et al, 2021 ). Thus, MS19 might also interact with the secreted HMGB1, leading to the functional inactivation by the induction of a conformational change.…”
Section: Discussionmentioning
confidence: 99%